Patience with final year students' academic stress at Universitas Kristen Satya Wacana - Pratiwi, Sari Indah; Soetjiningsih, Christiana Hari (Gema Wiralodra, 2024)
This study is quantitative correlational research which aims to determine the relationship between patience and academic stress. In this study, researchers used a purposive sampling technique with a total of 103 participant’s final year psychology students from the 2020 class of Psychology at Universitas Kristen Satya Wacana, who were working on their TA/thesis. The research instrument uses a patience scale and an academic stress scale. This research uses Spearman product moment correlation data analysis method. The results showed a correlation of r = -0,212 and a significance value of 0,016 (p <0,05). These results show that there is a negative relationship between patience and academic stress in final year students who are working on their thesis, which means that the higher the patience, the lower the academic stress. On the other hand, the lower the patience, the higher the academic stress. The results of this research can provide knowledge and coping for final year students who are working on their thesis so that they can increase their patience so that they can minimize academic stress when working on their thesis. This study associates the variable of patience with the variable of academic stress because the results of previous studies have not been conclusive, namely showing pro-contra results. In addition, the concept of patience is considered a positive character and is an important part of well-being which is one part of the study of positive psychology.